On n-fold implicative filters of lattice implication algebras - Young Bae Jun (International Journal of Mathematics and Mathematical Sciences)
We introduce the notion of n-fold implicative filters and n-fold implicative lattice implication algebras. We give characterizations of n-fold implicative filters and n-fold implicative lattice implication algebras. Finally, we construct an extension property for n-fold implicative filter.